Dampak Status Penguasaan Lahan Terhadap Pendapatan Petani Jagung Di Kabupaten Dompu Nusa Tenggara Barat - Mernawati Mernawati; Hayati Hayati; Muktasam Muktasam (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This study aims to determine the impact of land tenure status on the income of corn farmers in Dompu Regency, West Nusa Tenggara. The research method uses qualitative and quantitative methods. Data collection used an interview method with 60 respondents of corn farmers spread across the three main corn-producing districts in Dompu District, namely in Woja District, Kilo District and Pekat District. The results showed that there was not too much difference between the income of farmers who planted on their own land and on state land except for farmers who planted on leased state land. The average income of corn farmers who plant on their own land is Rp. 24,595,444, corn farmers plant on their own land and State land is Rp. 23,291,240, plant on State land is Rp. 23,523,800, and those who plant land on leased State land are Rp. 20,885,740.